Implementation of Human Resource Management In Relation to Employee Performance in Railway Public Transportation Services - Dewi Yuliati Indah; Syamsul Fadhila, Syifa Aulia; Pitaloka, Endang (Bulletin of Management and Business, 2025)
This study explores the implementation of human resource management, focusing on the effects of job mutation and workload on work stress and their subsequent impact on employee performance. The research was conducted within the KI unit of PT Kereta Api Indonesia (Persero), Bandung Head Office. The issue of decreased employee performance, particularly in aspects related to work behavior, prompted this investigation. A quantitative approach with descriptive and verification analysis methods was employed, utilizing a sample of 55 employees selected through probability sampling techniques. Data collection was conducted through structured questionnaires, and the analysis involved path analysis, multiple correlation, and coefficient of determination using SPSS 26. The findings indicate that both mutation and workload have significant effects on employee work stress, with workload being the more dominant contributing factor. Moreover, the study reveals a negative and significant relationship between work stress and employee performance. Specifically, excessive workload and unclear or mismatched job mutations lead to increased stress, which subsequently hinders employee performance in terms of productivity and behavioral consistency. The total influence of mutation and workload on stress was found to be 34.5%, while stress contributed 29.7% to variations in performance outcomes. These results underscore the importance of effective workload management and structured mutation planning in reducing stress levels and enhancing overall performance. Organizations, particularly in the public transportation sector, should consider these factors when designing HR strategies aimed at optimizing employee efficiency. Future studies are encouraged to incorporate qualitative insights to better understand the psychological dimensions underlying stress responses in organizational settings. Keywords: Employee Performance, Mutation, Work Stress, Workload